Detection of Malawi polyomavirus sequences in secondary lymphoid tissues from Italian healthy children: a transient site of infection. Issue 1 (December 2016) - Papa, N.; Zanotta, N.; Knowles, A.; Orzan, E.; Comar, M.
Abstract Background The novel Malawi polyomavirus (MWPyV) was initially detected in stool specimens from healthy children and children with gastrointestinal symptoms, mostly diarrhea, indicating that MWPyV might play a role in human gastroenteric diseases. Recently, MWPyV sequences were additionally identified in respiratory secretions from both healthy and acutely ill children suggesting that MWPyV may have a tropism for different human tissues. This study was designed to investigate the possible sites of latency/persistence for MWPyV in a cohort of healthy Italian children. Methods Specimens (n° 500) of tonsils, adenoids, blood, urines and feces, from 200 healthy and immunocompetent children (age range: 1–15 years) were tested for the amplification of the MWPyV LT antigen sequence by quantitative real-time PCR. Samples (n° 80) of blood and urines from 40 age-matched children with autoimmune diseases, were screened for comparison. Polyomaviruses JC/BK and Epstein-Barr Virus (EBV) were also tested as markers of infection in all samples using the same molecular technique. Results In our series of healthy children, MWPyV was detected only in the lymphoid tissues showing a prevalence of 6 % in tonsils and 1 % in adenoids, although with a low viral load. No JCPyV or BKPyV co-infection was found in MWPyV positive samples, while EBV showed a similar percentage of both in tonsils and adenoids (38 and 37 %). Conversely, no MWPyV DNA was detected in stool from babies with gastroenteric syndrome. With regards to autoimmune children, neither MWPyV nor BKPyV were detected in blood, while JCPyV viremia was observed in 15 % (6/40) of children treated with Infliximab. Urinary BKPyV shedding was observed in 12.5 % (5/40) while JCPyV in 100 % of the samples. Conclusions The detection of MWPyV sequences in tonsils and adenoids of healthy children suggests that secondary lymphoid tissues can harbour MWPyV probably as transient sites of persistence rather than actual sites of latency.